Diplomasi Kemanusiaan Indonesia Dalam Forum Asean (Association of Southeast Asia Nation): Studi Kasus Penanganan Krisis Rohingya Tahun 2017 -2025 - Melinda, Herawati; Prayuda, Rendi (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2026)
The phenomenon of Rohingya refugees arriving in Indonesia also demonstrates the practice of humanitarian diplomacy as classified by Minear and Smith, particularly in the aspects of negotiating access to aid and advocating for the protection of civil society. The research questions are: 1. How does Indonesian diplomacy encourage ASEAN to be involved in handling the Rohingya crisis? 2. What are the inhibiting factors faced by Indonesia in encouraging ASEAN to take collective action regarding the Rohingya crisis? The research method used is the Qualitative Descriptive method. The theory used is the theory of Indonesian Humanitarian Diplomacy. Based on the research results in the previous chapters, it can be concluded that Indonesia's humanitarian diplomacy in handling the Rohingya crisis in Myanmar through the ASEAN forum is a reflection of Indonesia's commitment to prioritizing humanitarian values ​​while maintaining regional stability. This diplomacy is carried out through a persuasive, dialogical, and cooperative approach, both through bilateral channels with Myanmar and through ASEAN multilateral mechanisms. Indonesia consistently strives to keep the Rohingya issue on the regional agenda by framing it as a humanitarian issue, not merely a domestic issue for Myanmar. This strategy allows Indonesia to continue playing an active role without directly violating the principle of non-interference which is a basic norm of ASEAN. In practice, Indonesia utilizes various forums such as the ASEAN Ministerial Meeting, the ASEAN Summit, and encourages the optimization of the role of the ASEAN Coordinating Center for Humanitarian Assistance (AHA Center) in distributing aid.